Tontonan, Tatanan, dan Tuntunan: Seni Pertunjukan Kuda Lumping di Kecamatan Bejen, Temanggung, 1965-1998 - Utama, Florentinus Galih Adi; Jiwangga, J.B. Judha; Parmadi, Eko Hari (Jurnal Sejarah Citra Lekha, 2025)
Kuda lumping is a form of folk performance that is deeply embedded in the lives of Javanese communities. In Bejen Subdistrict, Temanggung Regency, this performance tradition functions not only as popular entertainment but also as an integral part of everyday social life, developing distinctive characteristics that differentiate it from kuda lumping in other regions. In this area, at least three variants of kuda lumping dance movements are recognized: the classical-religious variant, the variant established through the 1972 consensus of the Regional Cultural Inspection Office (Idakeb) of Temanggung Regency, and the mass-oriented variant. These three variants are often performed together within a single performance repertoire. Despite its rich forms and long historical presence, historical studies that specifically examine the existence and development of kuda lumping performances in Bejen Subdistrict remain very limited. This study aims to reveal the dynamics of the development of kuda lumping performances in Bejen Subdistrict, Temanggung, while highlighting local inspirations that have shaped the cultural life of the community. A historical method is employed by placing written primary sources on an equal footing with oral traditions and traditional Javanese historiography, particularly Serat Kramaleya, a Javanese-language manuscript written in 1922 that contains descriptions of kuda lumping performances of its time. The findings indicate that kuda lumping performances in Bejen Subdistrict emerged alongside the development of Javanese-Islamic culture in Temanggung. Political upheavals following the events of the 30 September Movement in 1965 temporarily halted these artistic activities. However, in the subsequent period, kuda lumping experienced significant development. The formalization of kuda lumping dance concepts by the Temanggung Idakeb in 1972 marked a new phase, in which the art form came to function not only as entertainment but also as a medium for transmitting local wisdom and providing social education for the community.